THE INFLUENCE OF CAPITAL ADEQUACY RATIO, LOAN-TO-DEPOSIT RATIO, AND NET INTEREST MARGIN ON STOCK RETURN AT COMMERCIAL BANKS IN INDONESIA - Iskandar, Yusuf (Universitas Brawijaya, Indonesia, 2020)
The fluctuating conditions in the world economy have directly affected the investment to be uncertainty in several countries, including Indonesia whose investment was still not optimum, especially in the context of service companies such as banking companies. The less optimum investments that were closely associated with bank performance, especially with the stock return, encouraged this study to examine the effects of capital adequacy ratios, loan deposit ratios, and net interest margin on stock return at commercial banks in Indonesia. A total of 15 banks that met the criteria were taken as the sample. Data analysis was performed on banking companies listed on BEI (Indonesia Stock Exchange) in 2016-2018, employing the multiple regression analysis to test the proposed research hypotheses. The results showed that the capital adequacy ratio, loan-to-deposit ratio, and net interest margin significantly influence the stock return of banking companies.